ANTECEDENTS OF INTERNAL WHISTLEBLOWING INTENTIONS: EMPIRICAL STUDIES ON REGIONAL APPARATUS ORGANIZATIONS - Anissa Hakim Purwantini; Wulandari Wulandari (House of Management and Business (HOMBIS) Journal, 2022)
This study aims to examine the effect of ethical climate-egoism, ethical climate-benevolence, ethical climate principle, seriousness of violations, violators' status, personal costs and retaliation on internal Whistleblowing intentions. This research uses a sample of state civil servants who work in Regional Apparatus Organizations in Magelang City. The number of samples in this study were 136 respondents, based on the purposive sampling method, namely state civil servants who worked at least 2 years in Regional Apparatus Organizations in Magelang City. Hypothesis testing in this study used multiple linear regression. The results show that the ethical climate principle has a positive effect on internal Whistleblowing intentions. Meanwhile, ethical climate-egoism, ethical climate-benevolence, level of seriousness of violations, status of violators, personal costs and retaliation have no effect on Whistleblowing intentions.Keywords:Ethical Climate; Seriousness Level Of Violation; Violator Status; Personal Cost; Retaliation And Internal Whistleblowing Intention.